"What I cannot create, I do not understand": elucidating microbe–microbe interactions to facilitate plant microbiome engineering. (April 2023) - Geller, Alexander M; Levy, Asaf
Abstract : Plant–microbe interactions are important for both physiological and pathological processes. Despite the significance of plant–microbe interactions, microbe–microbe interactions themselves represent an important, complex, dynamic network that warrants deeper investigation. To understand how microbe–microbe interactions affect plant microbiomes, one approach is to systematically understand all the factors involved in successful engineering of a microbial community. This follows the physicist Richard Feynman's declaration: "what I cannot create, I do not understand". This review highlights recent studies that focus on aspects that we believe are important for building (ergo understanding) microbe–microbe interactions in the plant environment, including pairwise screening, intelligent application of cross-feeding models, spatial distributions of microbes, and understudied interactions between bacteria and fungi, phages, and protists. We offer a framework for systematic collection and centralized integration of data of plant microbiomes that could organize all the factors that can help ecologists understand microbiomes and help synthetic ecologists engineer beneficial microbiomes.